The Impact of Human Resource Slack on Digital Transformation in all China A-Share Listed Corporations: A Study of Mechanisms Based on Ownership - Lu, Ran (Journal of Cultural Analysis and Social Change, 2025)
The rapid development of China's digital economy has brought about the need for corporations to undergo digital transformation, and both manpower reserves and innovation capabilities play a role in the continuation of a digital transformation. This paper analyses the data of listed corporations on the Shenzhen and Shanghai stock exchanges over a period of 16 years from 2009, with a total of 28,619 samples, and measures the degree of digital transformation of corporations by their comprehensive performance in terms of ‘words’ and ‘deeds’, and it takes the degree of human resource slack as an independent variable, whilst adding ownership as a moderating variable to validate the difference between state-owned corporations and non-state-owned corporations in digital transformation. The robustness and endogeneity of the model are also examined, adding insights from different perspectives for Chinese corporations in the process of digital development.